DPP4 inhibition impairs senohemostasis to improve plaque stability in atherosclerotic mice - Allison B. Herman; Dimitrios Tsitsipatis; Carlos Anerillas; Krystyna Mazan-Mamczarz; Angelica E. Carr; Jordan M. Gregg; Mingyi Wang; Jing Zhang; Marc Michel; Charnae’ A. Henry-Smith; Sophia C. Harris; Rachel Munk; et al. (The Journal of Clinical Investigation, 2023)
Senescent vascular smooth muscle cells (VSMCs) accumulate in the vasculature with age and tissue damage and secrete factors that promote atherosclerotic plaque vulnerability and disease. Here, we report increased levels and activity of dipeptidyl peptidase 4 (DPP4), a serine protease, in senescent VSMCs. Analysis of the conditioned media from senescent VSMCs revealed a unique senescence-associated secretory phenotype (SASP) signature comprising many complement and coagulation factors; silencing or inhibiting DPP4 reduced these factors and increased cell death. Serum samples from persons with high risk for cardiovascular disease contained high levels of DPP4-regulated complement and coagulation factors. Importantly, DPP4 inhibition reduced senescent cell burden and coagulation and improved plaque stability, while single-cell resolution of senescent VSMCs reflected the senomorphic and senolytic effects of DPP4 inhibition in murine atherosclerosis. We propose that DPP4-regulated factors could be exploited therapeutically to reduce senescent cell function, reverse senohemostasis, and improve vascular disease.